Urgensi Hukum Dagang Dalam Penegakan Jual Beli Barang Online - Muslih, Muslih (VIVA THEMIS, 2024)
In the digital era, online shopping is increasingly popular and has become the main choice for many people. However, as online commerce develops, many problems emerge that need attention, such as fraud, transaction security, sending goods that do not match the description or are damaged when they arrive at the buyer. To solve this problem, it is important for sellers and buyers to communicate clearly with each other about the description of the goods, delivery conditions, etc. Commercial law has a very important role in enforcing online trade. Commercial Law is a regulation that regulates commercial activities between business entities, both in the form of buying and selling goods and services. In the field of online shopping, commercial law plays a role in protecting the rights and obligations of sellers and buyers as well as ensuring security and fairness in online transactions